Mercado de divisas y contagio financiero en Latinoamérica (2017)
The subprime crisis in the United States has been one of the most disastrous financial crises in recent decades. Economic impacts were shifted to other markets and other economies. The aim of this paper is to examine if there were episodes of contagion in the foreign exchange market in six Latin American economies: Argentina, Chile, Colombia, Brazil, Peru, Mexico, after disturbances originated in the United States. The DCC-GARCH methodology is chosen because of the advantages it has in implementing it, and it yields results that prove the existence of co-movements between exchange rate returns, with a high persistence, close to one. The coefficients of correlation between exchange rates increase in the period of crisis for the pairs: Colombia-Brazil, Colombia-Argentina, Colombia-Peru, Brazil-Argentina, Brazil-Peru, Brazil-Mexico, Argentina-Peru, Argentina-Mexico and Argentina-Chile. For the other combinations there is no evidence of contagion.